Efeitos do Treatment-Based Classification em pacientes com dor lombar: uma revisão sistemática com metanálise - Bastos, Robson Massi (2021)
Background: Low back pain is an important public health problem worldwide. Several researchers investigated stratification systems for patients with low back pain, in order to increase the size of the effect of interventions. Currently, the stratification model with the largest number of randomized controlled trials is the Treatment-Based Classification. Objective: To systematically review the effects of the Treatment-Based Classification system for patients with specific and non-specific, acute, subacute and chronic low back pain. Design: Systematic review. Outcome measures: The primary outcomes were pain intensity and disability. Secondary outcomes were quality of life, return to work and perceived global effect. Methods: The following electronic databases were searched: MEDLINE, EMBASE, PsycINFO, Global Health, CENTRAL, Cochrane Methodology Register, Health Technology Assessment Database, Cochrane Systematic Reviews, Web of Science, CINAHL, SPORTDiscus (via Ovíd), PEDro and registry World Health Organization (WHO) international trial database. We used the PEDro scale to assess methodological quality, the TIDieR Checklist to assess the quality on reporting of randomized controlled trials and the GRADE to measure the overall quality of evidence. Results: Twenty-one randomized controlled trials that included patients with non- specific low back pain, lumbar stenosis and sciatica (pooled n=2413) met the inclusion criteria. The pooled results from four randomized controlled trials (137 participants) found very low-quality evidence that manipulation is not better than mobility exercises for acute non-specific low back pain for disability (MD -8.18 points, 95% CI -21.69 to 5.32). Another meta-analysis, with three trials (pooled n=244 patients), shows that there is moderate quality of evidence that there is no difference between adding traction for sciatica for disability (MD -0.96 points, 95% CI -5.65 to 3.73). Other comparisons of single trials show that there is low quality of evidence that treatment-based classification is better than control groups for patients with acute and subacute low back pain but not for chronic low back pain patients. There is low quality of evidence from five trials that the directional preference subgroup is better than controls for lumbar stenosis. Conclusion: There is low quality evidence that treatment-based classification subgroups are better than approaches without a subgroup for patients with acute and subacute low back pain and for patients with spinal stenosis, but not for patients with chronic low back pain.